Maternity Care Preferences for Future Pregnancies Among United States Childbearers: The Impacts of COVID-19 - Gildner, Theresa E.; Thayer, Zaneta M. (Frontiers in Sociology, 2021)
The COVID-19 pandemic has impacted maternity care decisions, including plans to change providers or delivery location due to pandemic-related restrictions and fears. A relatively unexplored question, however, is how the pandemic may shape future maternity care preferences post-pandemic. Here, we use data collected from an online convenience survey of 980 women living in the United States to evaluate how and why the pandemic has affected women’s future care preferences. We hypothesize that while the majority of women will express a continued interest in hospital birth and OB/GYN care due to perceived safety of medicalized birth, a subset of women will express a new interest in out-of-hospital or “community” care in future pregnancies. However, factors such as local provider and facility availability, insurance coverage, and out-of-pocket cost could limit access to such future preferred care options. Among our predominately white, educated, and high-income sample, a total of 58 participants (5.9% of the sample) reported a novel preference for community care during future pregnancies. While the pandemic prompted the exploration of non-hospital options, the reasons women preferred community care were mostly consistent with factors described in pre-pandemic studies (e.g. a preference for a natural birth model and a desire for more person-centered care). However, a relatively high percentage (34.5%) of participants with novel preference for community care indicated that they expected limitations in their ability to access these services. These findings highlight how the pandemic has potentially influenced maternity care preferences, with implications for how providers and policy makers should anticipate and respond to future care needs.